ASPEK HUKUM KARTU INDONESIA SEHAT - Zahry Vandawati; Hilda Yunita Sabrie; Widhayani Dian Pawestri; Rizki Amalia (Universitas Airlangga, 2017)
Assurance is an important element in financial planning, but because of the low public awareness and myths that circulate in society around the insurance makes people reluctant to buy insurance products. Insurance is also known only for the upper middle class. On the other hand the realization of a prosperous society, one of which is assessed from the level of good public health. For that the government issued a compulsory social insurance in which the entire community on the mandate of the law shall be a participant of the program. Since 2011, the government has issued a regulation related to the National Social Security System and implemented through Badan Penyelenggara Jaminan Sosial (BPJS) in 2014. However, in the event it was due to political dynamics, the government under Jokowi leadership reissued Kartu Indonesia Sehat (KIS) A presidential regulation that functions the same as the existence of BPJS. This is what needs to be studied more deeply, because it is feared there will be overlapping roles and functions between BPJS and KIS them.